The antimicrobial resistance containment and surveillance approach - a public health tool - Gunnar S. Simonsen; John W. Tapsall; Benedetta Allegranzi; Elizabeth A. Talbot; Stefano Lazzari (The World Health Organization, 2004)
Antimicrobial drug resistance (AMR) is widely recognized as a global public health threat because it endangers the effectiveness of treatment of infectious diseases. In 2001 WHO issued the Global Strategy for Containment of Antimicrobial Resistance, but it has proved difficult to translate the recommendations of the Global Strategy into effective public health actions. The purpose of the Antimicrobial Resistance Containment and Surveillance (ARCS) approach is to facilitate the formulation of public health programmes and the mobilization of human and financial resources for the containment of AMR. The ARCS approach highlights the fundamental link between rational drug use and containment of AMR. Clinical management of human and animal infections should be improved through better disease control and prevention, high quality diagnostic testing, appropriate treatment regimens and consumer health education. At the same time, systems for supplying antimicrobial drugs should include appropriate regulations, lists of essential drugs, and functional mechanisms for the approval and delivery of drugs. Containment of AMR is defined in the ARCS approach as the continuous application of this package of core interventions. Surveillance of the extent and trends of antimicrobial resistance as well as the supply, selection and use of antimicrobial drugs should be established to monitor the process and outcome of containment of AMR. The ARCS approach is represented in the ARCS diagram (Fig. 2) which provides a simplified, but comprehensive illustration of the complex problem of containment and monitoring of AMR.